Craft museum visitors' interactive experiences, benefits and behavioural intentions: perspectives of Chinese parents. Issue 3 (3rd May 2020) - Shen, Haili; Wu, Mao-Ying; Wall, Geoffrey; Tong, Yixuan
ABSTRACT: Family visitors are important audiences for museums. This paper develops a model that examines the influence of Chinese family visitors' leisure experiences in museums on their behavioural intentions (BI) with their perceived benefits (mindful benefits and non-mindful benefits, MB and NMB) as the mediating variables. Based on the theoretical framework of an interactive experience model, parents' experiences in museums were divided into experience of existential authenticity (interaction with the exhibits) (EA) and experience of parents-children interaction (PCI). A total of 375 local family visitors at a cluster of craft museums in Hangzhou, China participated in the survey. The PLS-SEM analysis indicates that both EA and PCI have positive effects on perceived benefits. EA, which emphasises the personal interactions between visitors and exhibited objects as well as their intangible meanings, is found to be more powerful than PCI in shaping visitors' BI. MB and NMB differ in their influence on visitors' behaviours. Only MB is linked with visitors' BI. Further, MB partially mediates the relationship between EA and BI, and fully mediates the relationship between PCI and BI. Implications are offered to enhance family visitors' experiences through appropriate service management strategies.